DPP-IV Inhibitor-Associated Angioedema in Patient With Known History of ACE Inhibitor Angioedema - Chidinma Ejikeme MD; Chinedu Nwachukwu MD; John Luis Viechweg MD; Ifunanya Ejikeme; Micheal Brescia MD (SAGE Publishing, 2021)
The patient is a 69-year-old male with a past medical history of intellectual disability, hypertension, type 2 diabetes mellitus, and angiotensin-converting enzyme (ACE) inhibitor-associated angioedema who presented to the emergency department with difficulty breathing. On physical examination, the patient had significant facial edema. Nasal fiber-optic visualization revealed extensive airway edema involving the supraglottic region and the arytenoids. The patient was successfully intubated through the collective teamwork of ENT, anesthesia, and critical care teams. He was managed in the intensive care unit until recovery. Workup for markers for allergic causes of angioedema were within normal limits. Further investigation revealed that symptoms developed following the initiation of a dipeptidyl peptidase 4 (DPP-IV) inhibitor. The angiotensin-converting enzyme and DPP-IV play a significant role in the metabolism of bradykinin and substance P to their inactive metabolites. The complex interplay between the enzymes in the high-molecular-weight kininogen (HWMK) system may increase the risk of angioedema in patients with a known history of ACE inhibitor-associated angioedema when placed on a DPP-IV inhibitor. This case report highlights the pathophysiology involved.